2021
DOI: 10.3389/fphar.2021.583975
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin Upregulates microRNA-186 and Inhibits the TLR4-Mediated MAPKs/NF-κB Pathway to Relieve Steroid-Induced Avascular Necrosis of the Femoral Head

Abstract: Steroid-induced avascular necrosis of the femoral head (SANFH) is caused by the death of active components of the femoral head owing to hormone overdoses. The use of lipid-lowering drugs to prevent SANFH in animals inspired us to identify the mechanisms involving Atorvastatin (Ato) in SANFH. However, it is still not well understood how and to what extent Ato affects SANFH. This study aimed to figure out the efficacy of Ato in SANFH and the underlying molecular mechanisms. After establishment of the SANFH model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…SANFH is one of the most common hip pain diseases with an increasing incidence in recent years [1]. VEGF is an important angiogenic factor that regulates the proliferation, migration, and vascularization of VECs and plays a key role in bone formation and healing [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SANFH is one of the most common hip pain diseases with an increasing incidence in recent years [1]. VEGF is an important angiogenic factor that regulates the proliferation, migration, and vascularization of VECs and plays a key role in bone formation and healing [3].…”
Section: Discussionmentioning
confidence: 99%
“…Steroid-induced avascular necrosis of the femoral head (SANFH) is common non-traumatic osteonecrosis, which is a progressive pathological process caused by high-dose and/or long-term use of dexamethasone (Dex) or other glucocorticoids (GC) [1]. The main characteristics of SANFH are femoral head degeneration, bone trabecula or bone marrow necrosis, extensive bone marrow edema, and adipocyte hyperplasia [2].…”
Section: Introductionmentioning
confidence: 99%
“…32 Additionally, miR-186 showed inhibitory activity against the TLR4/NF-κB pathway in a mouse model. 33 In addition to regulating the related pathways, miR-488 and miR-920 were reported to directly target IL-1β. 34 All the related miRNAs except miR-488 and miR-920 were detected in this study, and the expected changing trend was found for miR-17-5p, which were downregulated in the model group and subsequently upregulated by the peptide treatments, while the expressions of miR-223 and miR-186 were only increased in the GPSGRP group compared to that of the model group (Table S9†).…”
Section: Discussionmentioning
confidence: 99%
“…19–21,45 Among the 49 differentially abundant genera identified in this study, genera Lactobacillus , Bifidobacterium and Enterococcus catalyze the hydrolysis of conjugated BAs to preserve the metabolic balance of BA, 46 genera Lactobacillus and Bifidobacterium converted tryptophan to indole and its derivatives, 47 and genera Lactobacillus , Akkermansia , Eubacterium and Blautia generated SCFAs by the degradation of dietary fiber. 33 Spearman's correlation analysis indicated that both Lactobacillus and Eubacterium correlated with four miRNAs, and genera related to the metabolism of SCFAs, tryptophan and BA were totally correlated with 17, 7 and 12 miRNAs (Table S10†), proposing the vital roles of microbiota metabolites between the gut microbiota and miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…As the major source of osteoblasts, BMSCs are important contributors to the bone tissue repair process. The abnormal osteogenic differentiation of BMSCs is an important cause of bone metabolism-related diseases, including osteoporosis[ 2 , 3 ]. O-linked β-N-acetylglucosaminylation (O-GlcNAcylation) is an important post-translational modification in which involves the attachment of a single O-linked N-acetylglucosamine (O-GlcNAc) moiety to Ser or Thr residues of cytoplasmic, nuclear, and mitochondrial proteins.…”
Section: Introductionmentioning
confidence: 99%